2019
DOI: 10.1155/2019/8356872
|View full text |Cite
|
Sign up to set email alerts
|

Physicobiochemical Characteristics and Chondrogenic Differentiation of Bone Marrow Mesenchymal Stem Cells (hBM-MSCs) in Biodegradable Porous Sponge Bovine Cartilage Scaffold

Abstract: Tissue engineering had been believed to overcome the limitation of cartilage lesions treatment. Nowadays the studies focus on using mesenchymal stem cells in scaffold. A biodegradable porous sponge bovine cartilage scaffold is expected to have the physicobiochemical characterization to promote chondrogenic differentiation of hBM-MSCs. Scaffold from bovine cartilage was printed in 5 mm diameter sponge, categorized into nondecellularized (SBCS) and decellularized (DSBCS). Physical characteristics (pore diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A high porosity in the range of 80−90% is optimal for in vitro cellular adhesion and migration along with the exchange of nutrients and oxygen. 37 The printed constructs were then characterized physicochemically and mechanically. The swelling ability and degradability of the constructs are two crucial requirements for the success of a scaffold/matrix in tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…A high porosity in the range of 80−90% is optimal for in vitro cellular adhesion and migration along with the exchange of nutrients and oxygen. 37 The printed constructs were then characterized physicochemically and mechanically. The swelling ability and degradability of the constructs are two crucial requirements for the success of a scaffold/matrix in tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that in repairing and protecting damaged cartilage, MSCs can be loaded on the scaffold to successfully generate cartilage (90). MSCs mainly improve cartilage function and repair cartilage damage from two aspects.…”
Section: Regeneration and Repair Signaling Mechanism Of Mscs In Damag...mentioning
confidence: 83%
“…A pore size of 100-300nm provided an environment conducive to cell metabolism. 23 Gelatine solvent possessed a pore size between 58nm and 475nm. 24 A pore 5-200nm in diameter was identified in the alginate solvent.…”
Section: Discussionmentioning
confidence: 99%